An In-Vitro Study Effect of Adding Silica Gel on Surface Hardness of Phosphate-Bonded Investment Material (Mustansiria Dental Journal, 2024)
Background: Only a few research have been undertaken to assess the influence of nanoparticles on the surface hardness of thermal investment materials. As a result, the current investigation was carried out to determine the influence of silica gel agents on the surface hardness of dental phosphate investment material at various percentages. Materials and methods: in this investigation, commercially available phosphate-bonded refractory investment material (Zetavest fine) and Silica gel powder (Himedia-India) were used. The specimens were manufactured and split into four groups (n=16): specimens without silica gel substance; specimens with 1% silica gel material; specimens with 2% silica gel material; and specimens with 3% silica gel material. A hardness test was performed with the use of an indenter durometer (Shore D). Surface hardness characteristics were analysed using A way ANOVA (post-hoc Tukey) test with a p-value of ≤0.05 indicating significance. Results: The surface hardness of investment specimens with 1%, 2%, and 3% silica gel powder before heating were comparable and have shown substantial differences from the specimens with non-additive. Conclusion: Silica gel of 1, 2, and 3% can improve the phosphate-bonded surface hardness.